Nanosheets of an Organic Molecular Assembly from Aqueous Medium Exhibit High Solid‐State Emission and Anisotropic Charge‐Carrier Mobility. Issue 10 (23rd December 2016) - Ghosh, Samrat; Philips, Divya Susan; Saeki, Akinori; Ajayaghosh, Ayyappanpillai
Abstract : A π‐conjugated amphiphilic diketopyrrolopyrrole (PDPP‐Amphi ) forms crystalline 2D supramolecular nanosheets in water when compared to that from methyl cyclohexane. These nanosheets exhibit high fluorescence quantum yield in the solid‐state with anisotropic charge‐carrier mobility of 0.33 cm 2 V –1 s –1 .